Simulation of Bacterial Cellulose by Acetobacter Xylinum 0416 Using Superpro DesignerÂ® - Syafiqah Kamarudin, Nur; Abdul Rahman, Norliza; Sahaid Kalil, Mohd.; Kartom Kamarudin, Siti (International Journal of Engineering and Technology, 2019)
Bacterial cellulose (BC) is a non-toxic biopolymer that is used as a raw material in food, textile and medical industries. The production cost of BC comprises the price of labor, raw materials, taxes and manufacturing supplies. In BC manufacturing, the fermentation media culture comprises between 50-65% from the total production rate. To reduce the production cost, other types of fermentation media culture should be studied, and mature coconut water is chosen in this research. Mature coconut water is considered as waste and it is estimated to be discarded 5.3 m3/day mainly in the coconut processing industry. In this research study, mature coconut water is used as a Â Â Â Â Â Â fermentation medium because it helps to reduce the price, easy to handle and found easily in the country. The optimization study was used in order to produce BC in large amount with a minimum fee. To conduct the optimization study, the pH of mature coconut water was adjusted to pH 4, 5 and 6 by using acetic acid (CH3COOH) or sodium hydroxide (NaOH) with incubation temperature of 32Â°C. The result indicates pH 4 produces the highest harvested BC with 2.277g dry weight. By using this result, pH 4 was chosen to be used as a media in the fermentation process. For industrial purposes, BC production must be carried out in the industrial scale. Before real industrial scale is conducted, process simulation should be done to simulate several processes and produce the desired end product at low cost, low energy and good product specifications. The simulation software named as SuperproDesignerÂ® was used to select the unit operation of a plant, to observe the total BC production and also the cost of BC production. This simulation was used to run three selected process alternatives named as alternative 1(Design by Prades et al.); 2 (Design by Norliza et al.) and 3(Design by Kerala Institute). After conducted the simulation, alternative 2 shown the cheapest BC production which is Â Â Â Â Â Â Â Â Â RM 170/kilogram compared to alternative 1 and 3.Â Â